(untitled) (Al-Farooq Journal of Sciences, 2026)
The political elite constitutes one of the key analytical foundations in political science. This study examines this concept through theoretical grounding, as well as by analyzing its effects within the political system. The research adopts both the descriptive-analytical approach and the comparative method, through the study of political elites in Tunisia and Morocco. The first section is devoted to presenting the concepts and theoretical approaches that explain the notion of the elite, while the second section addresses the analysis of the roles played by elites within the political system, whether in terms of political decision-making or in shaping public policies, culminating in their application to the two case studies. The study concludes that the political elite represents a central actor in the structure of the political system, given its possession of resources of power and influence. However, the nature of its roles and its effectiveness within the political system remain dependent on the political and institutional context, and vary from one system.